PROBLEMATIKA KEBIJAKAN DALAM MENGEMBANGKAN KOLEKSI DI PERPUSTAKAAN PERGURUAN TINGGI - Batriatul Alfa Dila (Jurnal Pustaka Ilmiah, 2019)
The paper gives a view to librarians to find out the problem of policy in the processof developing collections in high-rise library. This paper focuses on finding solutionsto policy problems in developing collections in high-education libraries, to determinethe success in developing library materials in the high-rise library. At the writingof this paper the method is more specific by using a literature review. The steps thatmust be carried out are as follows: 1. Urgency of collection development policies, 2.Carrying out activities that have been deemed by the library, 3. Involving users in theprovision of voluntary collections, 4. Planning the selection of library materials tobe provided in the library. the process of procuring a collection of library materialsthat is relevant to be provided in the library, 6. Always evaluating library materials tosupport success in the development of library collections. Constraints and solutionsfaced in developing collections, with the emergence of this paper provide new insights/ new ideas in providing the best solutions for the stages in developing collections inthe high-rise library.